2018
DOI: 10.1093/jas/skx049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ruminal acidosis and short-term low feed intake on indicators of gastrointestinal barrier function in Holstein steers

Abstract: The objective of this study was to determine effect of ruminal acidosis (RA) and low feed intake [LFI] on the regional barrier function of the gastrointestinal tract. Twenty-one Holstein steers were fed for ad libitum intake for 5 d (control [CON]), fed at 25% of ad libitum intake for 5 d (LFI), or provided 2 d of ad libitum intake followed by 1-d of feed restriction (25% of ad libitum intake), 1 d where 30% of ad libitum dry matter intake (DMI) was provided as pelleted barley followed by the full allocation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 63 publications
3
24
0
1
Order By: Relevance
“…In the present study, the increase of Occludin in colonic epithelium was basically consistent with the results of studies by Pederozoli et al [63] and Tao et al [41]. Reasons for the difference may be related to severity of SARA challenge, experimental animals, different dietary structures and the degree of damage to the intestinal epithelium.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the increase of Occludin in colonic epithelium was basically consistent with the results of studies by Pederozoli et al [63] and Tao et al [41]. Reasons for the difference may be related to severity of SARA challenge, experimental animals, different dietary structures and the degree of damage to the intestinal epithelium.…”
Section: Discussionsupporting
confidence: 92%
“…As such, we speculate that ruminal biopsies collected closer in time to the grain overload might have revealed a proinflammatory response associated with the initial stages of inflammation, and this speculation is supported by the model in Aschenbach et al (2019). Indeed, recent work from our laboratory (Pederzolli et al, 2018) reported an upregulation in TLR4 and TLR2 in rumen papillae of steers and lambs 24 h following an acidosis challenge, indicating a proinflammatory response. Future work incorporating earlier time points is needed to further investigate the effects observed in the present study.…”
Section: Discussionsupporting
confidence: 65%
“…Expression levels of rumen epithelial barrier genes Claudin-4 and ZO-1 are significantly lower in the cold season than in the warm season ( P < 0.05). Some studies have shown that when the feed intake of ruminants decreases, permeability of the gastrointestinal tract barrier increases ( Zhang et al, 2013a , b ; Pederzolli et al, 2018 ). Claudin-4 and ZO-1 , as the main components of the rumen epithelial barrier, control the permeability of this barrier, thereby regulating the absorption of nutrients and preventing entry of harmful substances ( Zhang et al, 2018 ; Aschenbach et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%